Lead‐free Double Perovskite Cs2AgIn0.9Bi0.1Cl6 Quantum Dots for White Light‐Emitting Diodes. Issue 2 (28th November 2021) - Zhang, Yuqing; Zhang, Zehao; Yu, Wenjin; He, Yong; Chen, Zhijian; Xiao, Lixin; Shi, Jun‐jie; Guo, Xuan; Wang, Shufeng; Qu, Bo
Abstract: Perovskite‐based optoelectronic devices have attracted considerable attention owing to their excellent device performances and facile solution processing. However, the toxicity and intrinsic instability of lead‐based perovskites have limited their commercial development. Moreover, the provision of an efficient white emission from a single perovskite layer is challenging. Here, novel electrically excited white light‐emitting diodes (WLEDs) based on lead‐free double perovskite Cs2 AgIn0.9 Bi0.1 Cl6 quantum dots (QDs) without any phosphor are fabricated for the first time. Density functional theory calculations are carried out to clarify the mechanism of absorption and recombination in Cs2 AgIn0.9 Bi0.1 Cl6 with Bi‐doping breaking the parity‐forbidden transition of the direct bandgap. Microzone optical and electronic characterizations reveal that the broadband emission of Cs2 AgIn0.9 Bi0.1 Cl6 QDs originates from self‐trapped excitons, and luminescent properties are unchanged after the film deposition. The QD‐WLED exhibits excellent Commission Internationale de L'Eclairage color coordinates, correlated color temperature and relatively high color rendering index of (0.32, 0.32), 6432 K, and 94.5, respectively. The maximum luminance of 158 cd m −2 is achieved by triphenylphosphine oxide passivation, and this lead‐free QD‐WLED exhibits a superior stability in ambient air with a long T 50 ≈48.53 min. Therefore, lead‐free perovskite Cs2 AgIn0.9 Bi0.1 Cl6 QDs are promising candidates for use in WLEDs in the future. Abstract : Neatly structured lead‐free double perovskite Cs2 AgIn0.9 Bi0.1 Cl6 QDs with a photoluminescence quantum yield (PLQY) of 31.4% are synthesized through hot‐injection method. The electrically excited white light‐emitting diodes (WLEDs) based on Cs2 AgIn0.9 Bi0.1 Cl6 QDs are fabricated for the first time, exhibiting excellent Commission Internationale de L'Eclairage (CIE) color coordinates, correlated color temperature, and a relatively high color rendering index of (0.32, 0.32), 6432 K, and 94.5, respectively.